An Analysis of Schubert's "Der Neugierige": A Tribute to Greta Kraus - Beach, David (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1998)
This brief study is a tribute to Greta Kraus who taught for many years in the Faculty of Music, University of Toronto. It is a personal interpretation of a single song, "Der Neugierige" from Franz Schubert's Die schöne Müllerin, following the linear approach developed by Heinrich Schenker, with whom Greta studied many years ago in Vienna. Greta had maintained her interest in Schenker's ideas, particularly their practical application to performance issues, throughout her long and industrious teaching career.